Alternative pathway activation of complement by African trypanosomes lacking a glycoprotein coat - Ferrante, A.; Allison, A.C. (Wiley, 1983)
Summary An in vitro culture Trypanosoma congolense cell line was established using the mammalian cell feeder layer system. One of the principle characteristics of this parasite was its ability to multiply in culture at 35°C, as an uncoated trypanosome (lacking a glycoprotein surface coat) unlike the original blood stream form from which it was derived. This trypanosome was lysed when incubated in normal human serum in contrast to the parasite which possessed a surface coat. The lytic reaction was inhibited by EDTA but not EGTA and occurred in C2‐deficient serum, demonstrating the involvement of the alternative pathway of complement activation. Similar results were obtained with procyclic forms of T. congolense and T. brucei brucei which also lacked surface coats. The results suggest that the glycoprotein surface coat protects the parasite by masking sites on the plasma membrane which are capable of promoting alternative pathway activation.